2009
DOI: 10.1111/j.1475-2743.2009.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of humic acid on water retention and nutrient acquisition in simulated golf putting greens

Abstract: Humic substances are frequently applied to creeping bentgrass (Agrostis palustris Huds.) on golf putting greens to improve turf health and are marketed to enhance nutrient acquisition and possibly aid in retaining water in drought prone environments, but information on the role of humic substances in increasing soil water retention is limited. Additionally, it is difficult to separate the beneficial effects of nutrients and other ingredients added to commercial humic formulations from the effects of the pure h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
8
0
1
Order By: Relevance
“…In contrast, Van Dyke et al. (2008, 2009) found that applications of humic acid decreased soil moisture and shortened the time between irrigation. Soil nutrient concentrations ranged from 10.4 to 12.2 mg kg −1 , 45.8 to 56.7 mg kg −1 , 206.3 to 243.8 mg kg −1 , 1,894.5 to 2,205.9 mg kg −1 , and 3.9 to 5.2 mg kg −1 for P, K, Mg, Ca, and Zn, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…In contrast, Van Dyke et al. (2008, 2009) found that applications of humic acid decreased soil moisture and shortened the time between irrigation. Soil nutrient concentrations ranged from 10.4 to 12.2 mg kg −1 , 45.8 to 56.7 mg kg −1 , 206.3 to 243.8 mg kg −1 , 1,894.5 to 2,205.9 mg kg −1 , and 3.9 to 5.2 mg kg −1 for P, K, Mg, Ca, and Zn, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…Changes in physical soil properties can be difficult over short-term studies and normally have a slow response to management changes [3,5]. However, these results are different from Van Dyke et al [36,59], who found that humic acid applications decreased soil volumetric water content and increased irrigation frequency. Although there were no changes in soil physical properties during this experiment, long-term humic fertilizer studies should be conducted to see if there would be any changes over a greater time period.…”
Section: Turfgrass Soil Healthmentioning
confidence: 92%
“…Creeping bentgrass 16% root mass [35] Creeping bentgrass 21% root length [36] Tall Fescue (Schedonorus arundinaceus (Schreb.) Dumort.…”
Section: Turfgrass Average Increase (%) Compared To Nontreated Control Referencementioning
confidence: 99%
“…Earlier research has explored the benefits of humic substances on turfgrass. Applications of humic products on creeping bentgrass (Agrostis stolonifera L.) increased root dehydrogenase activity, root growth and weight, physiological health, antioxidant concentrations, turf quality, germination rate, and percent cover [31][32][33][34][35][36][37][38][39]. Humic substances improved antioxidant concentrations, recovery or tolerance to heat injury, transplant quality, and root weight of tall fescue [Schedonorus arundinaceus (Schreb.)…”
Section: Introductionmentioning
confidence: 99%